Little pig, bigger trouble - Tharlet, Eve (London : Picutre Book Studio, 1992)
Henri the pig's penchant for getting into trouble involves him with a cake-aholic cow and runaway car.
TR/PS
Keywords: Pigs -- Fiction; Children stories